2019
DOI: 10.17557/tjfc.564087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mycorrhizal Fungi on Sesame Productivity Under Water Stress in Low-Input Agriculture System

Abstract: Arbuscular mycorrhizal fungi are organisms that cause to enhance the resistance of having fungi to water stress. To survey the effects of various levels of water deficit and two kinds of mycorrhizal fungi on quantitative and qualitative traits of sesame (Sesamum indicum L.) cultivars, an experimental using factorialsplit plot design was carried out with three replications in the research field of Agricultural Research Center, West-Azerbaijan in 2015 and 2016 cropping seasons. The main plots (factor A and B) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the study of He et al inoculation of mung bean plants with G. mosseae and G. caledonium under drought stress increased plant growth by 1.99 and 1.80 times, respectively 37 . Gholinezhad and Darvishzadeh 38 , reported that sesame grain yield was increased by 25 and 33% due to G. intraradices and G. mosseae inoculation, respectively. This was related to the positive effects of mycorrhizal inoculation on phosphorus uptake, longer leaf shelf life, maintaining and increasing leaf size and also improving photosynthesis by retaining higher chlorophyll content 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of He et al inoculation of mung bean plants with G. mosseae and G. caledonium under drought stress increased plant growth by 1.99 and 1.80 times, respectively 37 . Gholinezhad and Darvishzadeh 38 , reported that sesame grain yield was increased by 25 and 33% due to G. intraradices and G. mosseae inoculation, respectively. This was related to the positive effects of mycorrhizal inoculation on phosphorus uptake, longer leaf shelf life, maintaining and increasing leaf size and also improving photosynthesis by retaining higher chlorophyll content 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have investigated the potential of AMF to promote the accumulation of bioactive compounds in oil plants 11 13 . Gholinezhad and Darvishzadeh investigating the effects of two AMF species on grain yield and oil content of 8 local sesame cultivars and reported that AMF inoculation, especially with G. mosseae , improved grain yield and quality traits of sesame seeds under drought stress and well-watered conditions 38 . Igiehon et al found that the content of fatty acids in seeds of soybean plants were increased by mycorrhizal inoculaion under drought stress 13 .…”
Section: Discussionmentioning
confidence: 99%